Relationship between dynamic balance and spatiotemporal gait symmetry in hemiplegic patients with chronic stroke - Chang-Man An, MSc, PT; Young-Lan Son, MSc, PT; Young-Hyun Park, MSc, PT; Sung-Jun Moon, MSc, PT (World Scientific Publishing, 2017)
Background: Poor dynamic balance, which is common after stroke, may affect gait function. In particular, spatiotemporal asymmetrical gait patterns may occur in hemiplegic patients after stroke. Objective: This study aimed to assess the relationship between dynamic balance and spatiotemporal gait symmetry in patients with chronic hemiplegic stroke. Methods: To calculate symmetry ratios for step length (spatial parameter) and swing time (temporal parameter), 41 patients with chronic stroke walked at a comfortable speed. The dynamic balance measures included limit of stability (LOS) during standing and heel-to-heel base of support (H-H BOS) during gait. Analysis of correlations between various measures was performed. Results: The overall LOS score correlated with temporal gait symmetry (r=0.66). The forward, backward, paretic, and non-paretic direction LOS scores were related to temporal gait symmetry (r=0.38â0.62). The H-H BOS was correlated with temporal (r=â0.63) and spatial (r=â0.36) gait symmetries. Other dynamic balance variables were not significantly correlated with spatial gait symmetry. Conclusion: Thus, control of dynamic balance abilities is related to the magnitude of temporal gait symmetry. This observation suggests that rehabilitation strategies that improve dynamic balance may enhance temporal gait symmetry in post-stroke patients. Keywords: dynamic balance, heel-to-heel base of support, spatiotemporal gait symmetry, stroke